The impact of the manufacturing sector not attracting millennials in South Africa - Mthabini, Christopher (My University, 2018)
The research paper aims to determine the role of millennials in the manufacturing sector and the impact that this generation has on the future of manufacturing. The focus of the study is to identify the challenges that millennials face in the manufacturing sector as well as their expectations in the workplace, and to establish retention strategies that organisations can use to attract and retain this generation in the sector. South Africa’s manufacturing industry needs talented human resources that can sustain the industry without relying on importing technical skills from other countries, and the millennials form an integral part of the current workforce in the country. The study was conducted on millennials aged 22 to 37 years who are currently employed in the manufacturing and supporting sectors in Gauteng and Mpumalanga. A qualitative research method with open-ended questions was used to gather the information, while Microsoft Excel advance software was used for the data analysis after the coding of the responses. A total of 29 interviews representing the four different racial groups in South Africa in different career levels within their organisations were conducted. This generation has realistic expectations from their jobs such as innovation, leadership, development, benefits, recognition, technology, career growth and work-life balance. The findings about the millennials and the manufacturing sector from the study were used to recommend solutions and strategies that employers in the sector can use to attract and retain this generation of employees. With the future of manufacturing being threatened by not having new talent entering the sector and the current aging workforce nearing retirement without transferring their skills, it is imperative for the industry to nurture the millennials to form an integral part of the manufacturing sector. A partnership between the government and the manufacturing sector is key for the development and growth of the country.
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2018